2020
DOI: 10.3390/e22111248
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Unfavorable Driving States in Electroencephalography Based on a PCA Sample Entropy Feature and Multiple Classification Algorithms

Abstract: Unfavorable driving states can cause a large number of vehicle crashes and are significant factors in leading to traffic accidents. Hence, the aim of this research is to design a robust system to detect unfavorable driving states based on sample entropy feature analysis and multiple classification algorithms. Multi-channel Electroencephalography (EEG) signals are recorded from 16 participants while performing two types of driving tasks. For the purpose of selecting optimal feature sets for classification, prin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 30 publications
(32 reference statements)
0
7
0
Order By: Relevance
“…SampEn is suitable for feature detection in small sample datasets and has little dependence on data length, which is suitable for real-time online detection [40]. Studies have shown that the SampEn method is able to extract fatigue features from EEGs [63,64].…”
Section: Vmd-mmse Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…SampEn is suitable for feature detection in small sample datasets and has little dependence on data length, which is suitable for real-time online detection [40]. Studies have shown that the SampEn method is able to extract fatigue features from EEGs [63,64].…”
Section: Vmd-mmse Methodsmentioning
confidence: 99%
“…Additionally, as a non-linear processing method, entropy is also widely used in the detection of driving fatigue [36][37][38]. Compared with the mutlifractality method [39,40], MMSE can extract EEG features on a time scale, and the data length required by the MMSE method is shorter in terms of EEG processing. Consequently, for the special situation of driving fatigue detection, the MMSE method can better meet the needs of traffic safety.…”
Section: Introductionmentioning
confidence: 99%
“…( ) = { (0), (1), (2) … ( )} (14) where ( ) = ( ( ) , ( ), ( )) (0 ≤ ≤ ). Two kinds of errors are encountered during data collection: 1.…”
Section: B Data Preprocessingmentioning
confidence: 99%
“…However, there are some limitations, such as the camera's field of view, the complexity of target background, the intensity of light, and the privacy of the user. With the development of sensor technology, non-visual motion recognition technology has been developed rapidly, such as Hidden Markov Model (HMM) [12], Support Vector Machine (SVM) [13], Principal component analysis (PCA) [14], K-Nearest Neighbor (KNN) [15], Neural Network (NN), Singular value decomposition (SVD), and Wavelet packet transform (WPT). Most of these algorithms use surface electromyography (SEMG) signal acquisition sensor and inertial sensors in the process of data collection.…”
Section: Introductionmentioning
confidence: 99%
“…In a real-time environment, it is important to detect and monitor driver behavior to save human lives. To resolve this problem, there were many automatic driver fatigue detection systems [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 ] developed in past studies. Several computer vision-based applications were developed in the past to detect and predict driver fatigue.…”
Section: Study Backgroundmentioning
confidence: 99%